2014
DOI: 10.1021/am4048464
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Approach toward Inverse Opals with Linear and Nonlinear Optical Functionalities

Abstract: Three-dimensionally ordered macroporous materials have unique structural and optical properties, making them useful for numerous applications in catalysis, membrane science, and optics. Accessible and economic fabrication of these materials is essential to fully explore the many possibilities that these materials present. A new templating method to fabricate three-dimensionally ordered macroporous materials without overlayers is presented. The resulting structures are freestanding inverse opals with large-area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…The 21st century has also been marked by the rapid emergence of metamaterials and photonic crystals. , They both have an artificial periodical structure and have been proposed for use in many applications including SHG. , Recently, Pawlak et al , showed the potential of eutectic forming systems as an alternative to metamaterials and photonic crystals. Self-organized eutectic solidification, by its nature, can result in a very interesting spatial distribution of several materials with adequate geometrical motifs, which may afford enhanced electromagnetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…The 21st century has also been marked by the rapid emergence of metamaterials and photonic crystals. , They both have an artificial periodical structure and have been proposed for use in many applications including SHG. , Recently, Pawlak et al , showed the potential of eutectic forming systems as an alternative to metamaterials and photonic crystals. Self-organized eutectic solidification, by its nature, can result in a very interesting spatial distribution of several materials with adequate geometrical motifs, which may afford enhanced electromagnetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, binary IOs without overlayers were obtained. Demeyer et al employed the sandwich approach to obtain freestanding polymer IOs without overlayer for linear and nonlinear optical functions . Wang et al have developed a co‐self‐assembly approach to synthesize crack‐free CCs, during which the formation of overlayer could also be avoided through control of amount of the co‐assembling materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Because the periodicity of the colloidal crystal template is on the order of hundreds of nanometers, the resulting highly ordered porous (inverse opal) materials interact with visible light, leading to optical diffraction following Bragg diffraction. [1][2][3][4][5] Because the periodicity of the colloidal crystal template is on the order of hundreds of nanometers, the resulting highly ordered porous (inverse opal) materials interact with visible light, leading to optical diffraction following Bragg diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in the development of highly ordered porous functional structures through colloidal crystal templating in the elds of optics, chemical sensing, and micro-uidics. [1][2][3][4][5] Because the periodicity of the colloidal crystal template is on the order of hundreds of nanometers, the resulting highly ordered porous (inverse opal) materials interact with visible light, leading to optical diffraction following Bragg diffraction. [6][7][8] Inverse opal hydrogel structures are especially attractive because a hydrogel may swell or shrink in aqueous solution upon physical and chemical stimuli by changing its dimensions, which leads to spectral shis in the Bragg diffraction wavelength and structural color change.…”
Section: Introductionmentioning
confidence: 99%